Making Consistency More Consistent: A Unified Model for Coherence, Consistency and Isolation - Zhang, Irene; Szekeres, Adriana (Workshop on Principles and Practice of Consistency for Distributed Data (PaPoC), 2018)
Ordering guarantees are often defined using abstract execution models. Unfortunately, these models are complex and make different assumptions about system semantics. As a result, researchers find it impossible to compare the ordering guarantees of coherence, consistency and isolation. This paper presents a simple, unified model for defining ordering guarantees that is sufficiently general to model a wide range of systems, including processor memory, distributed storage, and databases. We define a new single constraint relationship, result visibility, which formalizes the ``appears to execute before'' relationship between operations. Using only result visibility, we define more than 20 ordering guarantees from different research areas, including PRAM, snapshot isolation and eventual consistency session guarantees. To our knowledge, these definitions form the broadest survey of ordering guarantees using a single constraint in the current literature.